Aggressive males are more attractive to females and more likely to win contests in jumping spiders - Kwek, Bernetta Zi Wei (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2021)
10.1016/j.anbehav.2021.06.030